Common mistakes in pronouncing silent letters for English education students - Mira Andini; Ekaningsih, Nur (Indonesian Journal of Education and Pedagogy, 2025)
Mispronunciation of silent letters remains a persistent challenge for English Education students due to the irregularities and complexities of English phonology, often leading to confusion and communication difficulties. This study aims to examine common mistakes in pronouncing silent letters among English Education students and to identify which silent letters are most problematic. Using a quantitative approach, a pronunciation test was conducted with 50 students at Islamic Private University in Semarang, Indonesia. Participants were asked to read sentences containing silent letters, and the resulting data were analyzed to identify mispronunciations and calculate their frequency and percentage. The results revealed that the silent letter “l” was the most frequently mispronounced (23.00%), while “u” had the lowest mistake rate (1.60%). These findings highlight the varying levels of difficulty posed by different silent letters, suggesting that pronunciation instruction should prioritize those with higher mistake rates to enhance students’ accuracy and overall proficiency.